Light Supplement and Carbon Dioxide Enrichment Affect Yield and Quality of Off‐Season Pepper. (1st September 2017) - Li, Xiaojie; Kang, Shaozhong; Li, Fusheng; Zhang, Xiaotao; Huo, Zailin; Ding, Risheng; Tong, Ling; Du, Taisheng; Li, Sien
Abstract : Core Ideas: Carbon dioxide enrichment and light supplement significantly increased the photosynthetic rate, yield, and water use efficiency. Carbon dioxide enrichment reduced fruit nutrition quality, whereas light supplement improved it. Applying light supplement and a CO2 concentration of 550 μmol mol −1 can optimize yield and quality. Off‐season vegetable crops in a greenhouse need supplementary light intensity and CO2 concentration to obtain good growth and fruit quality. The objective of this study was to investigate the effects of supplementary light intensity and CO2 concentration on the photosynthesis, yield, and fruit quality of fresh hot pepper (cultivar Meite). Two light intensities—supplementary (SLI) and natural (NLI) light intensity with the averaged photosynthetic active radiation of the whole growth period of 463 and 233 μmol m −2 s −1, respectively—and 4 CO2 concentrations (400, 550, 700, and 900 μmol mol −1 ) were conducted on pepper planted in pots in phytotrons over the autumn and winter seasons in the arid Northwest region of China. Results showed that: (i) CO2 enrichment significantly increased the net photosynthetic rate ( P n ), water use efficiency (WUE), yield parameters, and fruit storage qualities, but decreased the fruit nutrition qualities to different extents. (ii) SLI increased P n, WUE, and fruit nutrition qualities to different extents, and increased fruit yield per plant (FYPP) by 157%. (iii) The treatment with SLI and a CO2 concentration of 550 μmol mol −1 can maximize the overall quality of pepper fruits and significantly increase FYPP with a first ranking in the technique for order of preference by similarity to the ideal solution (TOPSIS) method. Therefore, the yield of pepper grown in the off‐season was increased and fruit quality was maintained by SLI and moderately increasing CO2 concentration (550 μmol mol −1 ).